EFFECT OF DIFFERENT DOSES OF ZINC IN CHILDREN WITH ACUTE WATERY DIARRHOEA (The Research of Medical Science Review, 2025)
Background: Diarrhea is the passage of loose or watery stools at least thrice in 24 hours.Diarrheal illness is the second leading cause of child mortality; among children younger than five years of age worldwide, it caused over 500,000 estimated deaths in 2017. Objective: To evaluate the effect of different doses of zinc (10 mg and 20 mg daily) on the duration, stool frequency, and adverse effects in children with acute watery diarrhea. Material and methods: This Randomized controlled trial was conducted at Department of Pediatrics, Ittefaq trust Hospital, Lahore during-----------------------------. Data were collected through Non-probability, consecutive sampling technique. A total of 60 children aged 1–5 years with acute watery diarrhea were randomly divided into two groups. Group A received 10 mg zinc daily for 14 days, while Group B received 20 mg zinc daily for the same duration. Results: Children in Group B (20 mg zinc) had a significantly shorter mean diarrhea duration (3.5 ± 0.9 days) compared to Group A (10 mg zinc, 4.2 ± 1.1 days; p = 0.02). Stool frequency <3 was achieved in 67% of Group B compared to 20% of Group A by Day 5 (p < 0.001). Vomiting episodes were higher in Group B (27%) than in Group A (10%), but the difference was not statistically significant (p = 0.08). Conclusion: It is concluded that 20 mg zinc supplementation is more effective than 10 mg in reducing diarrhea duration and normalizing stool frequency. While mild side effects such as vomiting were more frequent with the higher dose, the benefits outweigh the risks.